Pembelajaran Berbasis Standar Proses: Mewujudkan Paradigma Baru Pembelajaran - Siregar, Nurhelila; Suhendra, Ade (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
This paper describe about learning on standart of process for to realize new paradigm of learning. Learning is the core activity on education. Learning as in on standart of process have a set of criteria that must implemented as whole that constantly updated. Standart process on education is an important instrument in order to create learning process that explorated the potential students to achieve the learning objectives. Quality learning must be carried out actively and interactively to explore the potential of students.